Treatment of ruptured intracranial aneurysms yesterday and now - Hammer, Alexander; Kunze, Stefan (PLOS ONE, 2017)
Objective This prospective study is designed to detect changes in the treatment of ruptured intracranial aneurysms over a period of 17 years. OPEN ACCESS Citation: Hammer A, Steiner A, Kerry G, Ranaie G, Baer I, Hammer CM, et al. (2017) Treatment of ruptured intracranial aneurysms yesterday and now. PLoS ONE 12(3): e0172837. doi:10.1371/ journal.pone.0172837 Editor: Helena Kuivaniemi, Stellenbosch University Faculty of Medicine and Health Sciences, SOUTH AFRICA Received: July 4, 2016 Accepted: February 10, 2017 Published: March 3, 2017 Copyright: © 2017 Hammer et al. This is an open access article distributed under the terms of the Creative Commons Attribution License, which permits unrestricted use, distribution, and reproduction in any medium, provided the original author and source are credited. Data Availability Statement: All data are within the paper. Funding: The authors received no specific funding for this work. Competing interests: The authors have declared that no competing interests exist. Methods We compared 361 treated cases of aneurysm occlusion after subarachnoid hemorrhage from 1997 to 2003 with 281 cases from 2006 to 2014. Specialists of neuroradiology and vascular neurosurgery decided over the modality assignment. We established a prospective data acquisition in both groups to detect significant differences within a follow-up time of one year. With this setting we evaluated the treatment methods over time and compared endovascular with microsurgical treatment. Results When compared to the earlier group, microsurgical treatment was less frequently chosen in the more recent collective because of neck-configuration. Endovascular treatment was chosen more frequently over time (31.9% versus 48.8%). Occurrence of initial symptomatic ischemic stroke was significantly lower in the clipping group compared to the endovascular group and remained stable over time. The number of reinterventions due to refilled treated aneurysms significantly decreased in the endovascular group at one-year follow-up, but the significantly better occlusion- and reintervention-rate of the microsurgical group persisted. The rebleeding rate in the endovascular group at one year follow-up decreased from 6.1% to 2.2% and showed no statistically significant difference to the microsurgical group, anymore (endovascular 2.2% versus microsurgical 0.0%, p = 0.11). Conclusion Microsurgical clipping still has some advantages, however endovascular treatment is improving rapidly.
Gesehen am 30.05.2018